2019
DOI: 10.1210/jendso/bvz017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dapagliflozin on Endothelial Dysfunction in Type 2 Diabetes With Established Ischemic Heart Disease (EDIFIED)

Abstract: Objectives To evaluate the effect of the sodium-glucose cotransporter 2 inhibitor (SGLT2-I) dapagliflozin on endothelial function in patients with high-risk type 2 diabetes mellitus (T2DM). Methods This was a prospective, double-blind, randomized, placebo-controlled, clinical trial of patients with T2DM with underlying ischemic heart disease who were receiving metformin and insulin therapy (n = 81). After 12-weeks of addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
0
35
1
Order By: Relevance
“…In the EDIFIED trial, a 12-week therapy with dapagliflozin, in addition to insulin and metformin therapies, resulted in significant reductions in HbA1c, fasting blood glucose, and surrogate markers of endothelial function. Furthermore, there was a significant association between reduction in HbA1c and improvement in FMD in the dapagliflozin group [ 49 ]. These observations together with our present findings should have an impetus on further investigations regarding the protective role of new anti-diabetic agents especially SGLT2 on endothelial function and their ability to suppress the progression of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the EDIFIED trial, a 12-week therapy with dapagliflozin, in addition to insulin and metformin therapies, resulted in significant reductions in HbA1c, fasting blood glucose, and surrogate markers of endothelial function. Furthermore, there was a significant association between reduction in HbA1c and improvement in FMD in the dapagliflozin group [ 49 ]. These observations together with our present findings should have an impetus on further investigations regarding the protective role of new anti-diabetic agents especially SGLT2 on endothelial function and their ability to suppress the progression of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The DEFENCE study found a significant improvement in endothelial function in patients with T2D receiving dapagliflozin 5 mg/day as an add-on therapy to metformin 750 mg/day [ 18 ]. Similarly, T2D patients with ischemic heart disease showed a significant reduction in surrogate markers for endothelial function following 12 weeks of dapagliflozin monotherapy [ 19 ]. An investigation by Solini et al suggested that dapagliflozin might have a protective cardioprotective effect in preserving vasodilating capacity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three previous studies in T2DM reported inconsistent dapagliflozin effects on FMD [ 22 24 ]. The first study showed improvement in FMD after two days of treatment [ 23 ]; however, the authors reported no effect after 4 weeks of treatment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a second trial, although FMD was not significantly changed in the intention-to-treat analysis, a post hoc analysis indicated that an improvement was detected in a subgroup of patients with HbA1c > 7.0% at baseline. In the last study, 12-week treatment with dapagliflozin was compared with placebo, and although the change in FMD was inversely proportional to the change in HbA1c (r = − 0.4; p = 0.017), there was no significant improvement in FMD after dapagliflozin [ 24 ]. The main limitations of these trials were the selection of patients with FMD close to normal values as well as the suboptimal and unbalanced reduction in blood glucose in the study arms [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation